The Jungle Book - "Wright, Diane Landolf"; , John Rowe (New York; Random House, 2008)
Adaptation of Rudyard Kipling's "The Jungle Book," focusing on stories that feature Mowgli, Baloo the bear, and Bagheera the panther
Keywords: Animals Fiction